Peran Film Animasi "Pocoyo" dalam Upaya Pengkondisian Imajinasi Anak Autis - Iska Dwi Athma Putri Rosyadi; Lies Neni Budiarti; Ruly Darmawan (Wimba : Jurnal Komunikasi Visual, 2012)
Pocoyo is a film that used as a trigger, especially in SDLB Autis Lab Univ. Malang. Autism is a kind of developmental disorder, and its diagnosis is based on certain criterias that have been previously defined. Generally, when people watch a film, there is a process imagination in them. All people, which is a normal one or has special needs, have imagination. It is because of humans are basically creative creature. Therefore, animated films Pocoyoâs role in conditioning autism imagination is important for further study. This master theses used qualitative approach in order to achieve that objective. Content Analysis, Visual Analysis, and Flow concept are used to find out the role of Pocoyo animated film in developing autism imagination. By using colouring work of subjects (child with autism), imagination that formed within children with autism are ascertainable. This research revealed that Pocoyo animated film could condition on subjectâs imagination. When he on colouring activity, there was âkomunikasi-dalamâ within him. Imagination was formed because the film has a blank background, and minimal property. Emptiness made subject feel free to fill it with imagination he had. Subject also had Flow experience, which can be seen in the totality of the coloring pictures. This totality raised because he might have seized the opportunity that offered by emptiness of Pocoyo animated film to be filled with a variety of imaginations.